Meta-Analysis: The Effect of Learning Methods on Students' Critical Thinking Skills in Biological Materials - Fuji Astutik; Erna Wijayanti (Universitas Cokroaminoto Palopo, 2020)
Critical thinking skills are important for students as they enable them to develop social, scientific attitudes, and solve practical problems. This study aims to identify learning methods that can be used to develop critical thinking skills. This research method is a meta-analysis using articles obtained from online journal databases. Data were analyzed quantitatively by calculating the effect size. Based on the results of the study, it can prove that (1) critical thinking skills effectively developed in high school students and (2) learning methods used to train students' critical skills are PjBL and GI.